Antecedents of Financial Behavior of MSME - Handayani, Anita (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have an important role in economic growth and development in Indonesia. MSMEs are an integral part of the national business world and have a strategic position, potential, and role in realizing national development goals. The way to achieve the goals above, it is necessary to have MSMEs that can survive in various conditions. Good management is needed in managing these MSMEs, one of which is the financial behavior of MSMEs because financial behavior is an individual's perception of controlling sources of funds (money). This research aims to analyze the role of financial factors that can influence the financial behavior of MSMEs. This research uses a quantitative method with a structural equation model. So, MSMEs need to have good financial behavior to maintain business continuity. The financial factors used in this research are Financial Literacy, Financial Attitude, Locus of Control, and Financial knowledge. The research results show that all the variables used have an impact on the financial behavior of MSMEs in Gresik.